Structural and microstructural properties of Cd₁-xZnxTe films deposited by close spaced vacuum sublimation - Znamenshchykov, Y.V.; Kosyak, V.V.; Opanasyuk, A.S.; Kolesnyk, M.M.; Grinenko, V.V.; Fochuk, P.M. (Functional Materials, 2016)
The structural properties (microstresses, texture, lattice parameter, coherent scattering domains size) and chemical composition of Cd₁₋xZnxTe (CZT) films with variable zinc concentration were studied. Films were deposited on molybdenum coated glass substrates by close spaced vacuum sublimation method. Properties of samples were investigated by X-ray diffraction, energy dispersive spectroscopy, scanning electron microscopy. Zinc concentration in CdZnTe layers was determined by the EDS and from the lattice parameter, according to the literature data. Namely, it was determined that the CZT films had following Zn concentrations: x = 0.09, x = 0.24, x = 0.30.